Translation Methods Used in Translating Harry’s House Album Songs Lyrics - Rahel Lamria Sitorus; Morada Tetty (TRANSFORM : Journal of English Language Teaching and Learning, 2023)
This study aimed at determining the methods used in translating song lyrics on Harry's house album on Indolirik YouTube channel. The theory used in analyzing the data is Newmark theory (1988) which explained that there were two approaches in translating text namely SL Emphasis (Domestication) in which the emphasis was on the source language and the other one was TL Emphasis (Foreignization) in which the emphasis was on the target language. Newmark (1988) also explained there were eight methods of translations, namely, word for word, literal, faithful, semantic, adaptation, free, idiomatic, and communicative translation. The researcher conducted a descriptive qualitative method in analyzing the data. The data were taken from the translation of song lyrics on Harry's house album on Indolirik YouTube channel, which consisted of 5 songs and 111 song lyrics. The findings of this research showed that there were 6 types of translation methods used by Indolirik YouTube channel in translating the lyrics. From the analyzed data, Indolirik YouTube channelused Literal translation (43,25%), Word-for-Word translation (5,41%), Free translation (10,81%), Idiomatic Translation (17,11%), and Communicative translation (23,42%).  It was also found that the translator mostly used the literal translation process, it means that the translation products focused on the source language in translating the song lyrics rather than the target one.